2021
DOI: 10.1177/14680874211030898
|View full text |Cite
|
Sign up to set email alerts
|

Influences of C5 esters addition on anti-knock and auto-ignition tendency of a gasoline surrogate fuel

Abstract: The research octane numbers and auto-ignition characteristics of a toluene primary reference fuel (TPRF), when blended with three C5 esters, γ-valerolactone (GVL), methyl butanoate (MB), and methyl crotonate (MC), were investigated on a cooperative fuel research (CFR) engine and a constant volume combustion chamber (CVCC). In fuel preparation, ethanol was used to improve the miscibility, and the total additive comprised 1/3 ethanol and 2/3 GVL/MB/MC on a molar basis. The experimental results first reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Details of the experimental apparatus can be obtained in the authors' previous studies. 17,18 Engine operational parameters in the RON and MON tests were controlled within the acceptable range defined by the standards ASTM D2699 19 and D2700, 20 respectively.…”
Section: Cfr Engine and Test Methodsmentioning
confidence: 99%
“…Details of the experimental apparatus can be obtained in the authors' previous studies. 17,18 Engine operational parameters in the RON and MON tests were controlled within the acceptable range defined by the standards ASTM D2699 19 and D2700, 20 respectively.…”
Section: Cfr Engine and Test Methodsmentioning
confidence: 99%
“…ε-caprolactone contains 6 carbon atoms in a cyclic ester structure. Based on the current production potential and higher carbon number of ε-caprolactone compared to GVL (an extensively researched lactone), 34,38,39 The possibility to utilise larger lactones, such as εCL, in diesel engines is therefore highly intriguing. This report is, to the best of our knowledge, the first example of the combustion of higher lactones in a compression ignition engine.…”
Section: Introductionmentioning
confidence: 99%
“…Because of those practical complications, a surrogate for gasoline fuels is widely used to perform and validate both experiments and computational modeling. 13,14 A wide range of studies have been conducted, primarily focused on the addition of hydrogen to a surrogate, involving a single component, e.g., iso-octane. 15 Mandilas et al 16 determined the S L o of iso-octane/hydrogen mixtures and found that at stoichiometric conditions, the S L o of i-C 8 H 18 /H 2 mixtures increased positively with the increased mass fraction of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have reported gasoline–hydrogen–air combustion characteristics because of commercial gasoline’s complex and variable composition. Because of those practical complications, a surrogate for gasoline fuels is widely used to perform and validate both experiments and computational modeling. , A wide range of studies have been conducted, primarily focused on the addition of hydrogen to a surrogate, involving a single component, e.g., iso -octane …”
Section: Introductionmentioning
confidence: 99%